2018
DOI: 10.1051/e3sconf/20186702016
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel deposit characterization on hot chamber test rig with biodiesel fuels (B20) and bioaditif essential oil (atsiri)

Abstract: In this study, the deposit formation of B20-NA biodiesel with the addition of bioadditive Essential Oil with different variations, B20 + Essential Oil 1:2000, B20 + Essential Oil 1:3000, B20 + Essential Oil 1: 4000 and B20 + Essential Oil 1:5000 method of hot plate drops to know the characteristics and mechanisms of deposit formation on each variation of fuel. The research is carried out by the deposition process and evaporation of Diesel fuels carried out repeatedly on a hot plate. The plate is heated with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Uy et al reported the nanostructures of gasoline fuel deposits, and compared major deposit particles from exhaust gases and from engine oil 6) . Bambang Sugiarto et al in his research to obtain the characteristics the formation of deposits in the combustion chamber where the B20 biodiesel sample is mixed with essential oil with a ratio of 1: 2000,1: 3000,1: 4000 and 1: 5000 7) . Baker et al in his research Effect of Fuel Additives on the composition and formation of deposits by spectroscopic analysis 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Uy et al reported the nanostructures of gasoline fuel deposits, and compared major deposit particles from exhaust gases and from engine oil 6) . Bambang Sugiarto et al in his research to obtain the characteristics the formation of deposits in the combustion chamber where the B20 biodiesel sample is mixed with essential oil with a ratio of 1: 2000,1: 3000,1: 4000 and 1: 5000 7) . Baker et al in his research Effect of Fuel Additives on the composition and formation of deposits by spectroscopic analysis 8) .…”
Section: Introductionmentioning
confidence: 99%